BRCA1‐Associated Protein 1 (BAP1) Immunohistochemical Expression as a Diagnostic Tool in Malignant Pleural Mesothelioma Classification: A Large Retrospective Study. Issue 11 (November 2016) - Righi, Luisella; Duregon, Eleonora; Vatrano, Simona; Izzo, Stefania; Giorcelli, Jessica; Rondón‐Lagos, Milena; Ascoli, Valeria; Ruffini, Enrico; Ventura, Laura; Volante, Marco; Papotti, Mauro; Scagliotti, Giorgio Vittorio
ABSTRACT : Introduction : Malignant pleural mesothelioma (MPM) is a highly aggressive disease with limited therapeutic options. Histological subtype remains among the most reliable prognostic factors, because the epithelioid subtype associated with the best prognosis and the sarcomatoid subtype with the worst. The biphasic subtype has an intermediate prognosis, but its definitive histological diagnosis may be challenging owing to the difficulty of assessing the neoplastic nature of the stromal component. Recent data identified BRCA1‐associated protein 1 gene ( BAP1 ) as one of the most frequently mutated genes in MPM. Immunohistochemical testing for BRCA1‐associated protein 1 (BAP1) has been proposed to be predictive for the detection of BAP1 mutation in neoplastic cells. The aim of the present study was to define the diagnostic usefulness of immunohistochemical determination of BAP1 in MPM, with clinicopathological correlation. Methods : A series of 143 MPMs were investigated for BAP1 protein expression in correlation with clinical and pathological data, including with a newly proposed nuclear grade. A pilot series of 20 selected cases were also investigated for BAP1 mutational status. Results : Negative nuclear staining for BAP1 occurred in 62% of MPMs (including 27% with a cytoplasmic pattern) and was significantly associated with the presence of BAP1 mutation, epithelioid subtype, and a better prognosis. In a subgroup of cases, the pattern of expression of BAP1 in stromal cells supported their distinction as reactive versus neoplastic, thus helping achieve the correct classification of biphasic histological subtype. Conclusions : We showed that BAP1 protein determination is a diagnostic tool to correctly distinguish biphasic MPM from epithelial subtypes with an atypical/activated reactive stroma and an independent prognostic parameter in MPM.